2021
DOI: 10.15258/sst.2021.49.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of high temperature on embryonic growth and seed germination of dill (Anethum graveolens)

Abstract: Temperature is the main exogenous factor that determines the growth, development and productivity of agricultural plants, including seed germination. In this work, we studied the thermosensitivity of heterogeneous dill seeds (Anethum graveolens). The study aimed to study the short-term (1-5 days) effect of high temperature (40°C) on the growth of the embryo and germination of dill seeds formed on different umbels of the mother plant. The growth of the embryo had a significant effect on seed germination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…Those plants were treated with the combination of stresses (HT+WL) for 7 consecutive days exposure. This present finding is similar with a study conducted by Martinez-Eixarch and Ellis [36], which reported that seed viability was most vulnerable by 7 days of exposure to high temperature (38C) in the 7 or 14 DAA, when histodifferentiation occurs. During seed development, seed are in the process into filling with its composition and this is influenced by various metabolic processes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Those plants were treated with the combination of stresses (HT+WL) for 7 consecutive days exposure. This present finding is similar with a study conducted by Martinez-Eixarch and Ellis [36], which reported that seed viability was most vulnerable by 7 days of exposure to high temperature (38C) in the 7 or 14 DAA, when histodifferentiation occurs. During seed development, seed are in the process into filling with its composition and this is influenced by various metabolic processes.…”
Section: Discussionsupporting
confidence: 93%
“…This low viability after mother plant stress is supported by Martínez-Eixarch and Ellis [35] who reported that the viability of Gleva seeds was reduced by extreme-temperature (38/34℃) treatments applied in the 7 or 14 d immediately after anthesis. Similarly, another study conducted by Bukharov et al [36] reported that the duration of heat at 40°C may lead to a decrease in viability of dill (Anethum graveolens) which vary from 1-5 days of exposure.…”
Section: Discussionmentioning
confidence: 84%
“…According to Bukharov et al (2021) who studied the short-term (1-5 days) effect of high temperature (40°C) on the growth of the embryo and germination of dill seeds, the degree of development of the embryo determines seed germination. The reported results showed that the less developed embryos in seeds from secondary umbels are more sensitive to high temperatures during dill seed germination.…”
Section: Seed Quality Parametersmentioning
confidence: 99%
“…In both seasons, high and low soil temperatures cause failure of field emergence or irregular emergence in this species that is grown by direct seeding and that has a long field emergence period, resulting in product loss (Zehtab-Salmasi et al, 2006;Ghassemi-Golezani et al, 2018). In addition, there have been reports about problems with the quality of the produced dill seeds, such as poor germination and slow and heterogeneous field emergence (Bukharov et al, 2021;Alan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation